Selectivity of gillnets for the capture of Selene peruviana and Peprilus medius in the Ecuadorian Pacific - Mendoza-Nieto , Kléver (2024)
In the Ecuadorian Pacific, Selene peruviana and Peprilus medius are target species for artisanal fishing caught with gillnets that constitute an important fishery resource for local consumption, given that they are highly valued species due to their low cost and their contribution of high biological value protein. However, no studies have determined selectivity in capturing these species. This study evaluates the selectivity of monofilament surface gillnets with mesh sizes of 3" (7.62 cm) and 3 ½" (8.89 cm), mostly used by artisanal fishers. Data were obtained from several fishing operations within the coastal zone of 8 nautical miles (nm) in Manabí, Ecuador, in 2017, between 6:00 pm and 6:00 am. Selectivity parameters and curves were evaluated through multi-model analysis using the SELEC method. The lognormal model showed the best fit with modal lengths of 24.23 and 21.96 cm for S. peruviana and P. medius, respectively, and selection factors of 3.23 and 3.11. The optimal mesh sizes were calculated at 7.20 and 6.91 cm, respectively, which are smaller than those commonly used by most local artisanal fishers. Therefore, it can be inferred that the size distribution of the captured species follows a lognormal distribution, suggesting that gillnets have a higher probability of capturing larger fish.